An Experimental Investigation on the Determinants of Online Hotel Booking Intention. Issue 6 (18th August 2017) - Park, Kwangsoo; Ha, Jooyeon; Park, Jeong-Yeol
ABSTRACT: Online hotel booking is a common practice among potential travelers. When booking a hotel room, potential travelers make their decisions by analyzing limited information, such as number of rooms sold at a specific price, availability of rooms, and consumer ratings. Considering the importance of information clues that facilitate potential travelers' decision-making, this study attempted to identify main effects and interaction effects of diverse information clues, such as scarcity, popularity, and consumer ratings, when booking a hotel room. Utilizing a 2Scarcity  × 2Popularity  × 2Ratings factorial design, popularity and consumer ratings had main effects on the booking intention. In addition, the interaction effect of scarcity and popularity was identified. More implications are discussed in the main body of this paper.